EVALUATION OF OXIDATIVE STRESS BIOMARKERS MDA AND SOD IN OCCUPATIONALLY EXPOSED ALUMINUM WORKERS IN ONITSHA, ANAMBRA STATE, NIGERIA - Okechukwu, C.A; Okpogba, A.N; Mbachu, N.A; Ezeugwunne, I.P (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Aim: This research study was conducted to evaluate oxidative stress biomarkers using malondialdehyde (MDA) and superoxide dismutase (SOD) in aluminum workers exposed to occupational hazards. Research Method: The participants were recruited from an industrial area in Onitsha and divided into two groups: an exposure group composed of workers occupationally exposed to aluminum and a control group without exposure. The method of Gutteridge and Wilkins, (1982) was used for the estimation of malondialdehyde levels. SOD activity was measured according to the method as described by Misra and Fridovich, 1972. Data were analyzed using SPSS version 25 (IBM, USA, 2018). Independent T-test, descriptive, statistics, and Spearman correlation were used to analyze the data. Results: The results showed a significant increase in MDA in the aluminum workers group (3.53±1.04) as compared to the control group (1.65±0.58) (p<0.005). The SOD levels were reduced in the aluminum workers (21.55±3.85) as compared with the control samples (24.12±3.54) (p<0.005), indicating an elevation of oxidative stress. The study results revealed a significant positive correlation between MDA levels, age and duration of exposure. The SOD levels revealed a nonsignificant negative correlation with age and a significant correlation with duration of exposure. Conclusion: The findings indicate that long-term occupational exposure to aluminum can lead to increased oxidative stress, as indicated by higher MDA levels and lower SOD levels